Мент поганый: [повести] / Николай Леонов - Леонов Николай Иванович (Серия "Черная кошка", 1997)
Экземпляры: ф.9 (2009) / Инвентарный номер: 44862 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л47 / ББК: 84(2Рос=Рус)6